Kesejahteraan Psikologis Perempuan Anggota PKK - Josephine Ondja; Olivia Hadiwirawan (Lembaga Penelitian Universitas YARSI, 2018)
PKK (Empowerment and Family) is one of organization in Indonesia that aim to increase community’s welfare through empowering women in community. This study was intended to describe psychological well-being of women who volunteered in PKK. This study used mixed methods sequential explanatory strategy, consisted of two phases, quantitative followed by qualitative. Quantitative data were collected from 78 women members of PKK in Tanjung Duren Utara Sub-District, Jakarta by using modified Ryff’s Short Version Scale of Psychological Well-being. The result from quantitative analysis was categorized and showed psychological well-being of member PKK are high category for autonomy, self- acceptance, purpose in life, positive relations with others, and personal growth dimension; moderate category for environmental mastery dimension. Three women who have high score categorization in purpose in life and self-acceptance dimension were selected and interviewed to describe the psychological well being. In qualitative analysis, the major themes emerged for purpose in life dimension was women devoted their life for family and society. Themes emerged for self-acceptance dimension was women who sincere (ikhlas) in doing their role in community. PKK could emerge as a vessel for women to achieve and maintain their psychological well being.